Chapter Regeneration of historic centers in Mediterranean cities: the case study of the Venice district in Livorno - Spagnoli, Valentina (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The article talks about an experience of design research, aimed at the regeneration of a portion of the waterfront of the city of Livorno, which is now fragmented and in a state of decay and strongly characterized by the presence of the contemporary fish market building. The research proposes a new spatial arrangement through the re-functionalization of the building and the design of all the access systems to the area, driveways, pedestrian and cycle paths, which can allow its proper use by citizens and tourists. The area is transformed from a transit place into a place of rest and meeting.